2004
DOI: 10.1177/216507990405200108
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perception of Their Work Environment, Health, and Well-Being

Abstract: The purpose of this analysis was to identify themes nurses expressed in open-ended comments at the end of a working conditions survey related to their work environment, health, and well-being. The nursing shortage, downsizing, and long working hours create challenges for nurses trying to deliver quality client care. In addition, nurses are experiencing high levels of physical injury in their work environments. Injuries on the job have led nurses to leave the workplace. Free form comments offered at the complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 24 publications
6
58
0
Order By: Relevance
“…Other relevant nurse staffing studies found a significant effect of higher nurse to patient ratios on nurse outcomes, including turnover, burnout, job dissatisfaction and intent to leave (Larrabee et al, 2003; Shaver & Lacey, 2003; Geiger-Brown et al, 2004; Kovner, Brewer, Wu, Cheng, & Suzuki, 2006). Much of the research on job satisfaction focused on how low staffing levels and heavy workloads may lead to nurse dissatisfaction and an increased likelihood nurses will leave their jobs.…”
Section: Introductionmentioning
confidence: 96%
“…Other relevant nurse staffing studies found a significant effect of higher nurse to patient ratios on nurse outcomes, including turnover, burnout, job dissatisfaction and intent to leave (Larrabee et al, 2003; Shaver & Lacey, 2003; Geiger-Brown et al, 2004; Kovner, Brewer, Wu, Cheng, & Suzuki, 2006). Much of the research on job satisfaction focused on how low staffing levels and heavy workloads may lead to nurse dissatisfaction and an increased likelihood nurses will leave their jobs.…”
Section: Introductionmentioning
confidence: 96%
“…Reports of LBP among nurses and other patient care workers range from 30–60%, 58 and may contribute to the exodus of nurses from this profession. 6, 9 …”
Section: Introductionmentioning
confidence: 99%
“…Both fatigue and sleepiness have been linked to performance decrements and decreased well-being and satisfaction among nurses, with implications for patient and nurse safety, nurse injuries and wellness, and nurse recruitment and retention (Barker and Nussbaum, 2011;Barker Steege and Nussbaum, 2012;Yip, 2001;Geiger-Brown et al, 2004;Lipscomb et al, 2004;Edell-Gustafsson et al, 2002;Josten et al, 2003;Taylor and Barling, 2004;Rogers et al, 2004;Carayon and Gurses, 2005). The importance of fatigue in nursing has been acknowledged by the American Nurses Association in a resolution stating that work-related fatigue in nurses is a critical factor in efforts to improve patient safety, quality of care and nurse safety (Implications of Fatigue on Patient and Nurse Safety, 2005).…”
Section: Quantitative Models Of Work-related Fatiguementioning
confidence: 99%